3D printed aluminum flat heat pipes with micro grooves for efficient thermal management of high power LEDs - Chao Chang (Nature Portfolio, 2021)
Abstract As the electronic technology becomes increasingly integrated and miniaturized, thermal management has become a major challenge for electronic device applications. A heat pipe is a highly efficient two-phase heat transfer device. Due to its simple structure, high thermal conductivity and good temperature uniformity, it has been used in many different industrial fields. A novel aluminum flat heat pipe, with micro-grooves, has in the present work been designed and fabricated by using a 3D printing technology. Aluminum powder was used as a raw material, which was selectively melted and solidified to form the shape of the heat pipe. The sintered aluminum powder increased the roughness of the inner surface of the heat pipe, and the designed micro-grooves further enhanced the capillary forces induced by the wick structure. The wettability, for the working fluid (acetone), was excellent and the capillary forces were sufficient for the working fluid to flow back in the pipe. The effects of working fluid filling ratio, on the heat transfer performance of the heat pipe, was also investigated. It was shown that a filling ratio of 10% gave the best heat transfer performance with the lowest thermal resistance. The 3D-printed flat heat pipe was, therefore, also tested for the thermal management of a LED. The temperature of the LED could be kept within 40 °C and its service life became prolonged.